Exploring the Potential of Nanoparticles in Biofuel Production: Challenges and Future Directions – A Comprehensive Review - Joy, Nivin; Mariadhas, Anish; Venugopal, Hariharan; Maria, Reshlin Rithan Raj; Venugopal, Jayaprakash; Jayaraman, Jayaprabakar (Recent Patents on Mechanical Engineering, 2025)
The utilization of nanotechnology and nanotechnology in contemporary society has garnered significant interest due to their captivating properties across various academic disciplines. The investigation and development of biodiesel production and fabrication using nanotechnology and nanomaterials have emerged as a central area of scholarly inquiry worldwide. Implementing strategies to accelerate biodiesel production is essential to its success; there is an increasing focus on utilizing state-of-the-art nanotechnology, which enables achieving maximum output while minimizing costs. Consequently, the investigation will center on using various nanomaterials and nanocatalysts to explore the manufacture of biodiesel from diverse materials. The examination of this research project will primarily focus on the culture of algae utilizing nanomaterials and the subsequent collection of lipids. Furthermore, the present investigation is intended to serve as a comprehensive examination of the foremost obstacles and prospective ahead-of-time enhancements regarding the utilization of biodiesel blended with nanoparticle additives in internal combustion engines. Additionally, this study will analyze existing patents related to nanomaterials and their role in biodiesel production. Furthermore, this essay will specifically address the problems related to the welfare of individuals and the environment in using nanomaterials in mass manufacturing biodiesel. Consequently, future producers, researchers, and academics stand to gain valuable insights from this study, as it offers a comprehensive understanding of the existing body of research on the application of nanoparticles and nanotechnology in making biodiesel, along with the advancements in enhancing its efficiency.
Keywords: nanotechnology